Realism and psychology : collected essays - Mackay, Nigel.; Petocz, Agnes. (Philosophy of History and Culture, 2011)
This book is a collection of new, published and revised essays on the place and value of scientific realism in psychology. Through critical analyses of contemporary psychology, essays argue that the realist requirements of a properly scientific psychology are often misunderstood even in the discipline's putatively scientific heart, with profound conceptual and empirical consequences. Against this, and in answer to recent calls to demonstrate the relevance of realism, the essays sketch the elements of a realist program: they discuss the recent history, development and principal features of a distinctive, thoroughgoing, realism for psychology: its theories, concepts, methods and applications. It thus aims to extend realism from philosophy to psychology, articulate a realist metatheory, clarify realism's relevance, and promote its discussion.